Censorship and framing in war journalism: the perspective of Rubem Braga's chronicles during the Estado Novo: - Cardoso Teixeira, Gisela (2024)
This article analyzes the act of silencing in war journalism, exploring the semantic effects produced by censorship in journalistic discourse. Based on the notions of silêncio fundante ("foundational silence", Orlandi, 1997) and news framing (Gitlin, 1980; Entman, 1993), it examines 15 chronicles by Rubem Braga on the participation of the Brazilian Expeditionary Force (FEB) in World War II. The study highlights how censorship during the Estado Novo emphasized Brazilian heroism while silencing casualties and strategic failures. Through textual analysis, it reveals the interaction between literature and journalism as creative resistance, shedding light on the political and ideological impacts of silencing in war narratives.